Internal Consistency and Convergent Validity of the Portuguese Versions of the Global Appraisal of Individual Needs–Initial and Short Screener: Validity of the Portuguese GAIN-I and SS - Garcia Claro, Heloísa (J Addict Nurs, 2016)
The goal of this article is to present evidence on the internal consistency and convergent validity of the Brazilian Portuguese versions of the Global Appraisal of Individual Needs–“Initial” and “Short Screener” versions. METHODS: One hundred sixty-eight individuals from an inpatient service and/or a community-based outpatient service located in São Paulo were interviewed using the Brazilian Portuguese versions of the instruments. The internal consistency of the instruments scales was computed, along with evidence for the convergent validity between corresponding subscales of the Initial and Short Screener instruments. RESULTS: Cronbach’s alpha values for both instruments’ total scale scores were greater than .7. The Short Screener scales showed strong-to-moderate correlations with corresponding subscales of the Initial. The General Individual Severity Scale from the Initial and Total Disorder Screener from the Short Screener have convergent validity with each other (ρ = 0.801). CONCLUSIONS: The Brazilian Portuguese instrument scales showed evidence for internal consistency and convergent validity performing similarly to the American English versions.